Svenskproducerat proteinfoder till slaktsvin - Nilsson, Hanna (SLU/Dept. of Animal Nutrition and Management (until 231231), 2011)
Soybean meal from South America is the most common protein feed used for animal production in Sweden. Production of soybean has negative effects on the environment and the transports from South America to Sweden causes considerable CO2 emissions. Therefore it is a growing interest in locally produced protein feed in Sweden. Protein feeds that are possible to grow in Sweden are rapeseed, peas, faba beans and lupins. Those are adapted to the Nordic climate and are perfect to grow in cereal rotations. However, these protein feeds contain antinational substances (ANS) that cause problems like growth depression for growing- and finishing pigs, and therefore limit their use as animal feed. The most common ANS in those crops are glucosinolates, tannins, proteasinhibitors, alkaloids, lectins, saponins, vicin and convicin. Other protein rich feed that can be used in pig production is meal or pellets of lucerne, a common forage crop in Sweden, and byproducts from ethanol production like stillage or dried distillers’ grains with soluble. The problem with stillage is that the farm has to be located close to the factory due to expensive transports. It is possible to produce feed that meets the nutrient requirements of growing and finishing pigs from locally produced feedstuffs. But the feed will be more expensive than feeds including soybean, therefore the pork price has to be higher from pig grown on Swedish produced feed.